EEG brain oscillations are modulated by interoception in response to a synchronized motor vs. cognitive task - Angioletti, Laura; Balconi, Michela (Frontiers in Neuroanatomy, 2022)
So far, little is known about how conscious attention to internal body signals, that is, interoception, affects the synchronization with another person, a necessary or required social process that promotes affiliations and cooperation during daily joint social interactions. The effect of explicit interoceptive attentiveness (IA) modulation, conceived as the focus on the breath for a given time interval, on electrophysiological (EEG) correlates during an interpersonal motor task compared with a cognitive synchronization task was investigated in this study. A total of 28 healthy participants performed a motor and a cognitive synchronization task during the focus and no-focus breath conditions. During the tasks, frequency bands (delta, theta, alpha, and beta bands) from the frontal, temporo-central, and parieto-occipital regions of interest (ROIs) were acquired. According to the results, significantly higher delta and theta power were found in the focus condition in the frontal ROI during the execution of the motor than the cognitive synchronization task. Moreover, in the same experimental condition, delta and beta band power increased in the temporo-central ROI. The current study suggested two main patterns of frequency band modulation during the execution of a motor compared with the cognitive synchronization task while a person is focusing the attention on one's breath. This study can be considered as the first attempt to classify the different effects of interoceptive manipulation on motor and cognitive synchronization tasks using neurophysiological measures.